Crystalline carbon nitride anchored on MXene as an ordered Schottky heterojunction photocatalyst for enhanced visible-light hydrogen evolution. (July 2021) - Li, Jinmao; Li, Jin; Wu, Congcong; Li, Zuhong; Cai, Liwei; Tang, Hong; Zhou, Zezhu; Wang, Guohong; Wang, Juan; Zhao, Li; Wang, Shimin
Abstract: Carbon nitride (CN) polymer is considered as a potential material for photocatalysis, but surfers from the low photoconversion efficiency due to its high defect density. Although the defects can be limited through the crystallization of CN, the photocatalytic activity of single-component photocatalyst is still restricted by the recombination of photoexcited carriers. In our work, the ordered Schottky heterojunction of heptazine-based crystalline carbon nitride (HCN) and Ti3 C2 MXene was successfully prepared through ionothermal method. The HCN/Ti3 C2 composites exhibit higher photocatalytic performance than pristine HCN. Particularly, the HCNT20 sample exhibits the highest photocatalytic H2 evolution activity, which is about 8 and 2 times higher than that of bulk CN and pristine HCN, respectively. The results of charge transfer dynamics and DFT calculation reveal that the photocatalytic enhancement mechanism is primarily attributed to the synergistic effects of crystallization of CN, excellent conductivity of Ti3 C2 and well-constructed Schottky heterojunction. Graphical abstract: Image 1